The Digital Literacy Level of Adolescent Free Sex Offenders in West Sumatra - Benny Benny; Nora Zulvianti (LPPM Universitas PGRI Sumatera Barat, 2020)
The issue of free sex is still a major problem in West Sumatra, especially among teenagers. One of the causes was the high level of exposure of sexual information from digital devices. Teenagers who did the free sex are suspected that they have low digital literacy. The measurement of teenagers' free sex digital literacy level would show a new consideration for the government or people in charge to increase the effectiveness of preventing the free sex behavior among teenagers. This study was conducted. It involved 38 free sex teenagers age 11-24. They consisted of 11 males and 27 females who live in Padang, Bukittingi, and Payakumbuh. By using the Steve Wheeler's digital literacy approach, it was found that the average level of free sex on teenagers in West Sumatra was 77.5 or on medium category. This finding at the same time refuted the initial hypothesis that stated the level of teenagers' free sex digital literacy was on low category. These differences could be a consideration because two expected elements of digital literacy to prevent the teenagers from negative effect could reach the lowest achievement if they are compared with other digital literacy elements. In addition, the huge pornography propaganda in internet has also become one of causes why the teenagers with medium digital literacy category still do free sex.